Immunoinflammatory response and bioactive potential of GuttaFlow bioseal and MTA Fillapex in the rat subcutaneous tissue - Delfino, Mateus Machado [UNESP]; Guerreiro-Tanomaru, Juliane Maria [UNESP]; Tanomaru-Filho, Mário [UNESP]; Sasso-Cerri, Estela [UNESP]; Cerri, Paulo Sérgio [UNESP] (Springer Nature, 2020)
To evaluate the effect of GuttaFlow bioseal (GFB) and MTA Fillapex (MTAF) in comparison with Endofill (EF) in the subcutaneous tissue. Polyethylene tubes with GFB, MTAF, EF or empty tubes (control group; CG) were implanted into subcutaneous of rats. After 7, 15, 30 and 60 days, the capsule thickness, inflammatory reaction, interleukin-6 (IL-6), vascular endothelial growth factor (VEGF), caspase-3, TUNEL-positive cells, von Kossa and ultrastructural features were evaluated. The data were statistically analyzed (p ≤ 0.05). At all periods, the number of IL-6- and VEGF-immunolabelled cells, and capsule thickness were lower in GFB than MTAF, which was lower than EF (p < 0.0001). At 60 days, the number of inflammatory cells was similar in GFB and MTAF (p = 0.58). Significant differences in the number of TUNEL- and caspase-3-positive cells were not observed among GFB, MTAF and CG whereas the highest values were found in EF specimens. The EF specimens exhibited several cells with condensed chromatin, typical of apoptosis. von Kossa-positive and birefringent structures were only observed in GFB and MTAF, suggesting the presence of calcite crystals. Taken together, these results show that cellular and structural damage induced by GFB and MTAF sealers were recovery over time. Moreover, these sealers express bioactive potential in subcutaneous tissue.